Landscape design for housing areas: a review - Mohd. Hussain, Mohd. Ramzi; Mohd Shahli, FitryNadia; Tukiman, Izawati; Zen, Ismawi (Medwell Journals, 2017)
This study presents the theoretical review of the importance of landscape design for housing areas. Landscape design has become a significant effect for humans as well as all living things in order to provide a conducive living environment. Innovative landscapes that incorporate ecologically ideas and strategic design may help to prevent from extensive building heat gain, reduce the energy and water consumption as well as produce the natural and healthy ambience to the surrounding. The study framework covers four main aspects which are issues related to the housing landscape design, landscape design perceived the value of housing, the current needs and demands of landscape design and policies related to the importance of landscape design in housing development. The aim of the study is to highlight the demand for the proper landscape design that should be provided in any housing development. It is hoped that the study will contribute to further enrich the landscape design innovation as part of green and sustainable housing planning and development.